KARAKTERISTIK ORGANOLEPTIK KERUPUK SUSU DENGAN TARAF PEMBERIAN BAKING POWDER YANG BERBEDA - Dyah Nurul Afiyah; Elvisa Ratna Devi (Universitas Islam Kadiri, 2016)
Milk chips were the type of snacks that favored by children and adults. This kind of snacks made from milk that has high nutrition value required by children and adults. Milk chips required many ingredient, such as baking powders. The objective of this research was to study organoleptic parameters of milk chips with different treatment of baking powders (0,1%, 0,3%, 0,5%, 0,8%, 1%). The result of organoleptic test showed that different treatment of baking powders significantly impact the crispiness of milk chips. The highest score of crispiness found in milk chips with 1% doses of baking powders. So, high doses of baking powders giving the high score of crispiness by organoleptic test. High doses of baking powders not effecting colors, taste and flavours of milk chips.